Children born to SLE and APS mothers. (October 2014) - Nalli, C; Iodice, A; Andreoli, L; Lojacono, A; Motta, M; Fazzi, E; Tincani, A
Background: Systemic lupus erythematosus (SLE) and antiphospholipid antibody syndrome (APS) are autoimmune diseases that affect women of childbearing age. Pregnancies in these patients carry several complications such as prematurity. Maternal IgG antiphospholipid antibodies (aPL) can cross the placenta but they don't generally cause any neonatal thrombotic event. Because of the incompleteness of the fetal blood-brain barrier, aPL could theoretically reach the fetal brain. Whether this can have an effect on brain development is still under investigation. Some studies performed in children of patients with SLE and/or APS showed an increased number of learning disabilities without impairment in intelligence level. Objectives: The objectives of this article are to evaluate the neurodevelopment outcome in 30 children (median age 9 years) born to mothers with SLE and/or APS with IgG anti-beta2-glycoprotein I during the third trimester of pregnancy and found positive for the same antibodies at birth. Methods: A neurological physical exam was performed in all children. We submitted some questionnaires to the mothers: the Child Behavior CheckList (CBCL) and a homemade set of questions obtained by a team composed of rheumatologists and pediatric neurologists. Intellectual functioning was determined by the Wechsler scale for corrected age. Results: In all children neurological physical exam and intelligence levels were found to be normal but mild behavior disorders and history of neurological manifestations were shown in three children. Conclusions: Offspring of patients with SLE and/or APS are generally healthy. We and others observed the occurrence of minor neurological disorders that might be related to maternal disease or to prematurity. The limited number of the available data on this sensitive issue supports the need for further studies.